AI for chronic pain in children: a powerful resource - Alessandro Vittori; Marco Cascella (BMC Pediatrics)
Abstract Given the lack of scientific evidence, chronic pain represents an arduous challenge, especially in the pediatric field. In this complex scenario, artificial intelligence (AI) could support diagnosis, therapy, and research. However, the great potential of AI must be combined with the protection of data and the most fragile patients.